Denomination: Algerian dialectal first name - BENMAHAMMED, Younes (Journal of Human Sciences, 2020)
We study in this paper the denomination question under the general linguistics point of vue and the special one through diverse approches of ancient ans modern specialists. Also, a semantic analysis is presented developing then the signification of algerian dialectal first name.